Tanggung Jawab Hukum Atas Penyalahgunaan Kartu Kredit Pemerintah Dalam Pengelolaan Keuangan Negara - Sarbini, Ilyas; Gufran, Gufran (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The study aims to identify and understand the legal responsibility for the misuse of government credit card holders in the country's financial management. This type of research is doctrinal legal research or normative legal research. The approach used is, the legal approach (statute approach), and the conceptual approach (Conceptual Approach). Data sources are sourced from primary legal materials, secondary legal materials and tertiary legal materials. The results of the study showed that legal responsibility for the misuse of government credit cards, can be processed legally by state administration; if by law the state administration indemnity of state financial losses is difficult to implement, it is taken by filing Civil damages in the District Court and or criminal charges can be filed